Building capacity for genomics in primary care: a scoping review of practitioner attitudes, education needs, and enablers - Dunlop, Kate L. A.; Singh, Nehal; Smit, Amelia K.; Morrow, April L.; Steinberg, Julia; Cust, Anne E.; Makeham, Meredith; Bonner, Carissa; Terrill, Bronwyn; Monrouxe, Lynn V.; Wilkinson, David; Sawleshwarkar, Shailendra; et al. (Frontiers in Medicine, 2025)
IntroductionImproving clinical capacity for genomics in primary care promises to lead to better health, but genomics uptake in the sector is slow and patchy. This review aimed to identify the attitudes of primary care practitioners (PCPs) and the education needs and enablers in applying genomics to inform priorities in education and implementation.MethodsSearches were conducted across Medline, Scopus, CINAHL, Embase, and Cochrane CENTRAL until November 2023. Barriers and enablers were mapped to the Theoretical Domains Framework and the Genomic Medicine Integrative Research Framework.ResultsA total of 52 studies were included, and the most frequently mapped domains from the Theoretical Domains Framework were ‘Knowledge’ (65.4% of papers), ‘Environmental context and resources’ (40.4%), ‘Skills’ (38.5%), and ‘Social/professional role and identity’ (32.7%). Four key implications were identified: knowledge as a major barrier and enabler, education to build capacity, uncertainty about the role of PCPs, and additional needs beyond education alone.DiscussionWhile PCPs are optimistic about genomics, long-standing barriers to delivery in primary care remain. Multifaceted, evidence-based education strategies, including interactive components to change behaviour, will help to address barriers. Clarifying the role of PCPs, referral pathways, and collaboration with tertiary genetics services will further build capacity for genomics delivery in primary care.